Histomorphological spectrum of fungal infections - Jandial, Roopali; Choudhary, Mehnaz; Singh, Kuldeep (International Journal of Research in Medical Sciences, 2019)
Background: Fungal infections have become very common resulting in a wide range of diseases from superficial infections to invasive fungal lesions. These organisms are now capable of affecting not only the immunocompromised patients but also healthy immune-competent individuals. All other non-culture methods except histologic method cannot detect all the types of fungi and are not available widely especially in developing countries like India. Methods: This retrospective study conducted in the department of Pathology for a period of 5 years. A total of 29 cases were studied. The aim of this study was to detect the type of fungal infections and their distribution according to age, sex, and organ involvement in histopathologic specimens received in our department. Results: Twenty-nine cases with fungal infections were studied. Of these (22; 75.8%) were males, (7; 24.1%) were females with male dominance. The cases displayed extensive range of age prevalence between 12 and 77 years. The most common type of fungal infection encountered in this study was mucormycosis. The most common site involved in infection was maxillary sinus. Maxillary sinus was the most common site for mucormycosis. Conclusions: The histopathologic examination can provide a swift provisional identification of infectious fungal organisms and remains the only existing reliable means to identify certain pathogens.